PERFORMA PERTUMBUHAN HARPATICOIDA Tigriopus sp. DALAM KONDISI KULTUR SEMI MASSAL DENGAN DIET MIKROALGA YANG BERBEDA - Suminto Suminto; Diana Chilmawati (Departemen Akuakultur FPIK UNDIP, 2018)
Tigriopus sp. is a copepod included harpacticoid ordo which is a live food organism for marine fish and shrimp larvae. The lack of information about the appropriate microalgae diet is an obstacle in the semi-mass culture of Tigriopus sp. The purpose of this study was to determine the effect of different microalgae diets and the type of microalgae diet which provides the best growth performance of Tigriopus sp. in semi-mass culture conditions. The experimental design used was a Completely Randomized Design (CRD) with 4 treatments and 4 repetitions namely Tigriopus sp. with a microalgae diet; A. Chlorella vulgaris; B. Tetraselmis chuii; C. Chaetoceros calcitrans; and D. Isochrysis galbana. The results showed that giving C. calcitrans microalgae diet has significant effect (p<0.05) and provides growth performance of Tigriopus sp. Best total density reached 9,75±0,50 inds.mL-1; specific growth rate of the population was 0,114±0,003 inds.day-1 and egg production was 9.26 ± 0.09 eggs.ind.-1 Keywords: Tigriopus sp., growth performance, semi-mass culture, microalgae diet